Positive Effects of Probiotics on Motor Coordination and Brain during Moderate and High-Intensity Exercise in Adolescent Female Mice - Park, Ki Jun; Kim, Junechul (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2021)
Objectives This study aimed to investigate the effects of probiotics on inflammatory cytokines, neurotransmitters, and motor functions during different levels of exercise.Methods Female adolescent mice (n=140) were divided into two groups, of which one group was fed probiotics and the other group was not. For both groups, three levels of exercise were conducted: non-exercise, moderate-intensity exercise, and high-intensity exercise. Probiotics acquisition and aerobic treadmill exercise were the main variables during the growth period. We evaluated motor function with a rotarod test and analyzed cytokines and neurotransmitters in the cerebellum.Results In acceleration mode, the moderate and high-intensity exercise groups showed longer running times than the non-exercise groups (P<0.001). Also, the probiotic-ingestion group had longer latency before falling than those who did not take probiotics in both the high-intensity and the non-exercise groups (P=0.002, P=0.002, respectively). In steady-state mode, the non-exercise group showed lower records compared with the moderate and high-intensity exercise groups (P=0.017, P=0.004, respectively). The inflammatory cytokine levels were high in the groups that performed moderate and high-intensity exercises, but the high levels were relieved in those taking probiotics. The GABA concentration was high for the exercise group and the probiotic-ingestion group.Conclusion Taken together, probiotics help improve motor skills during moderate and high-intensity exercise and help relieve inflammatory responses in the brain. Thus, we suggest that probiotics can be a useful supplement for brain and body development during exercise in adolescence.
Keywords: Probiotics; Motor Function; Cytokine; Neurotransmitter; Female Mice